Wideband bow-tie slot antenna with defected ground structure for efficient radio frequency energy harvesting - Usman Yau; Jun Jiat Tiang; Surajo Muhammad; Nazih Khaddaj Mallat; Isiyaku Yau (Bulletin of Electrical Engineering and Informatics, 2026)
This work proposes the design and performance assessment of a wideband bow-tie slot antenna specifically developed for radio frequency energy harvesting (RFEH). The design employs a self-complementary bow-tie configuration, integrated with a defected ground structure (DGS) and fractal elements, to achieve improved bandwidth (BW) and gain. It achieved -10 dB simulated (measured) BW of 2.50 GHz (2.10 GHz) over a frequency span of 0.80-3.30 GHz (0.80 to 2.90 GHz) respectively. The results cover a target fo, simulated and measured fractional bandwidth (FBW) of 122% and 114% respectively, with a peak realized gain of 6.42 dBi. The antenna also achieved a compact dimension of 126 mm × 90 mm (0.73 lamda g × 0.52 lamda g). It is finally integrated with a wideband RF-rectifier for the purpose of validation. The design enables continuous wireless power transfer (WPT) suitable for RFEH in internet of things (IoT) devices and sensor nodes.